Conservative treatment of recurrent symptoms of an incomplete, atypical femoral fracture associated with glucocorticoid, bisphosphonate, and denosumab therapy in a patient with chronic obstructive pulmonary disease. Issue 5 (3rd September 2019) - Lai, Kun-Hung; Chiang, Chih-Yung; Yang, Rong-Sen; Yang, Kai-Chiang; Wu, Chang-Chin
ABSTRACT: Background: Patients with chronic obstructive pulmonary disease have a high prevalence of osteoporosis, and different osteoporosis drugs are used to prevent fractures in these patients. Although the overall incidence of complete or incomplete, atypical femoral fracture (AFF) is low, long-term use of antiresorptive agents is associated with an increased risk of developing AFF. Methods: We present a patient with chronic obstructive pulmonary disease with recurrent symptoms of an incomplete AFF who had been treated with glucocorticoids, and sequentially with alendronate, zoledronic acid, strontium ranelate, raloxifene, denosumab and finally with teriparatide. The first episode occurred before osteoporosis therapies, the second after bisphosphonate treatments, and the third under denosumab. Results: Although her symptoms resolved along with gradually healing of fracture lines after conservative treatment without surgical intervention, progressive varus deformity of the proximal femur may have contributed to recurrence of AFF. Conclusion: Early treatment with anabolic agents and prophylactic fixation of incomplete AFF may alleviate symptoms and prevent recurrences.